Exploration of yeast candida zeylonoides with special references to probiotic activity isolated from mozzarella cheese - Shamshad, Ritwika (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.